2014
DOI: 10.1007/s13197-014-1408-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of digestive enzymes from de-oiled mackerel (Scomber japonicus) muscle obtained by supercritical carbon dioxide and n-hexane extraction as a comparative study

Abstract: The oil in mackerel muscle was extracted using an environmental friendly solvent, supercritical carbon dioxide (SC-CO2) at a semi-batch flow extraction process and an n-hexane. The SC-CO2 was carried out at temperature 45 °C and pressures ranging from 15 to 25 MPa. The flow rate of CO2 (27 g/min) was constant at the entire extraction period of 2 h. The highest oil extracted residues after SC-CO2 extraction was used for activity measurement of digestive enzymes. Four digestive enzymes were found in water solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…It has also been found that SC-CO 2 extraction had no deteriorating effects on seed proteins, whereas extraction of oil with organic solvents such as hexane, diethyl ether, chloroform or acetone leads to the denaturation of seed proteins (Stahl et al 1980). Our results are also similar to those of Asaduzzaman and Chun (2015), who found that PAGE protein bands were more prominent in SC-CO 2 treated mackerel residues than in n-hexane-treated samples, and attributed this to the lack of protein denaturation in SC-CO 2 treated samples. It was also demonstrated that there was no protein denaturation in the residues of mackerel viscera, squid viscera (Todarodes pacificus) and krill (Euphausia superba) after oil extraction using the SC-CO 2 method, and that the intensity of electrophoretic patterns between untreated control and SC-CO 2 treated samples were identical (Park et al 2008;Uddin et al 2009;Ali-Nehari et al 2012).…”
Section: Sds-pagesupporting
confidence: 91%
See 1 more Smart Citation
“…It has also been found that SC-CO 2 extraction had no deteriorating effects on seed proteins, whereas extraction of oil with organic solvents such as hexane, diethyl ether, chloroform or acetone leads to the denaturation of seed proteins (Stahl et al 1980). Our results are also similar to those of Asaduzzaman and Chun (2015), who found that PAGE protein bands were more prominent in SC-CO 2 treated mackerel residues than in n-hexane-treated samples, and attributed this to the lack of protein denaturation in SC-CO 2 treated samples. It was also demonstrated that there was no protein denaturation in the residues of mackerel viscera, squid viscera (Todarodes pacificus) and krill (Euphausia superba) after oil extraction using the SC-CO 2 method, and that the intensity of electrophoretic patterns between untreated control and SC-CO 2 treated samples were identical (Park et al 2008;Uddin et al 2009;Ali-Nehari et al 2012).…”
Section: Sds-pagesupporting
confidence: 91%
“…Konak et al (2014) showed that the defatted oat flours defatted using SC-CO 2 had more soluble protein than the oat flours prepared by other processing methods. Similarly, it was also reported that the SC-CO 2 extracted mackerel residues contained more soluble extracts including protein than the hexane extracted de-oiled mackerel residues (Asaduzzaman and Chun 2015).…”
Section: Total Soluble Solids Contentsmentioning
confidence: 80%
“…Based on these studies, the protease exhibits high catalytic activity and heat stability over a wide range of temperature (40 to 60 °C) and pH (6 to 11). Unfortunately, the presence of lipids in fish viscera reduces the efficiency of extracting, isolating, and purifying the enzymes (Kishimura and Hayashi 1999 ; Uddin et al 2009 ; Kim and Dewapriya 2014 ; Asaduzzaman and Chun 2015 ). Furthermore, the presence of lipids accelerates protein oxidation, resulting in detrimental protein quality (Matsushita et al 1970 ; Kanner and Rosenthal 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…These parameters indicate that DBLSC-CO 2 had no protein denaturation and had a similar protein content (including quality) to CBL. Similarly, Asaduzzaman and Chun (2015) demonstrated that the gel banding patterns of the protein of SC-CO 2 -treated mackerel residues were more prominent than those in n-hexane-treated samples. Uddin et al (2009) and Abdelkarder et al (2012) reported that no protein denaturation was found in SC-CO 2 -treated squid viscera and krill samples.…”
Section: Resultsmentioning
confidence: 84%
“…Similarly, Konak et al (2014) demonstrated that SC-CO 2 -defatted oat flour had a greater soluble protein content than flours produced using other processing methods. Asaduzzaman and Chun (2015) reported higher protein contents in the water soluble extracts of SC-CO 2 defatted mackerel residues than in samples extracted using hexane as the organic solvent. Adebowale et al (2005) postulated that the better solubility of defatted flour proteins from the Mucuna species was an indicator that they had promising food applications.…”
Section: Resultsmentioning
confidence: 94%